2005
DOI: 10.1091/mbc.e05-03-0243
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions Position Mso1p, a Novel PTB Domain Homologue, in the Interface of the Exocyst Complex and the Exocytic SNARE Machinery in Yeast

Abstract: In this study, we have analyzed the association of the Sec1p interacting protein Mso1p with the membrane fusion machinery in yeast. We show that Mso1p is essential for vesicle fusion during prospore membrane formation. Green fluorescent protein-tagged Mso1p localizes to the sites of exocytosis and at the site of prospore membrane formation. In vivo and in vitro experiments identified a short amino-terminal sequence in Mso1p that mediates its interaction with Sec1p and is needed for vesicle fusion. A point muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(70 citation statements)
references
References 57 publications
6
64
0
Order By: Relevance
“…Moreover, binding experiments performed with locked forms of Sec4 (e.g. Sec4-N133I) showed that they could also coprecipitate with Mso1 and the SNARE complex (62). This lends support to the idea that Mso1 and Sec4 interact during SNARE assembly.…”
Section: Discussionsupporting
confidence: 54%
“…Moreover, binding experiments performed with locked forms of Sec4 (e.g. Sec4-N133I) showed that they could also coprecipitate with Mso1 and the SNARE complex (62). This lends support to the idea that Mso1 and Sec4 interact during SNARE assembly.…”
Section: Discussionsupporting
confidence: 54%
“…Recent support for a homotypic vesicle fusion event came from the analysis of the ⌬mso1 mutant, which affects the function of Sec1 and SNARE complex formation in meiosis. In this case, unfused vesicles that are tightly docked to the meiotic plaque are visible (39). The comparison of this phenotype with the one in the ⌬spo14 mutant suggests that the vesicles at the SPBs appear to be much looser bound to the SPBs in the ⌬spo14 mutant.…”
Section: Discussionmentioning
confidence: 80%
“…It is thought that PSM formation is initiated by the fusion of vesicles at the SPB that generate an initial compartment, which then subsequently becomes enlarged and grows around the haploid nucleus to which it is connected via the SPB. Only recently support for this model came from the analysis of a ⌬mso1 mutant in which a block of PSM formation on the level of vesicle fusion at the SPB was visible (39).…”
mentioning
confidence: 99%
“…In wild-type cells, vps13 mutants that had small prospore membranes (35), ady4 mutants that had abnormal prospore membranes (41), and ady3 mutants, the average SPBGolgi apparatus distances were essentially the same. By contrast, in three different mutants that formed very small or absent prospore membranes, sso1, mso1, or sma1 (22,34,44), the distance from the SPB to the Golgi apparatus was much greater. Therefore, a shorter SPB-Golgi apparatus distance correlates with the presence of a prospore membrane.…”
mentioning
confidence: 79%